NILAI-NILAI PENDIDIKAN DAN FUNGSI CERITA RAKYAT WAK MENTUKNG RAJA RAKNG UTANT DUWOK MANSIA SASTRA LISAN DAYAK KUALATN KABUPATEN KETAPANG - Linawati, Linawati; Syam, Christanto; Totok, Antonius (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractBased on the Background of this Research, the researcher was interested in describing and analyzing the educational values and story functions of Wak Mentukng Raja Rakng Utant Duwok Mansia folklore,in which it is a Dayak Kualatn oral literature that has educational values. The general problems in this study were how the values of education, how it functions and how the implementation plan of the research results towards the educational values in Wak Mentukng Raja Rakng Utant Duwok Mansia folklore in schools. The method used in this research was descriptive qualitative method. The results of this study indicate that Wak Mentukng Raja Rakng Utant Duwok Mansia folklore has educational values, namely religious education values, moral education values, cultural education values, social education values and functions as an educator, entertainer, and moral guided. In this study, the researcher discussed the values of education and the story function of Wak Mentukng Raja Rakng Utant Duwok Mansia folklore. The results of this study can be used as literary learning material in senior high schools (SMA). It concluded that in Wak Mentukng Raja Rakng Utant Duwok Mansia folklore, there are Educational values (religious education values, moral education values, cultural education values and social education values), as it functions as educators, entertainers, and moral guided that can be used as a picture of life and as a literary learning material at school.Keywords: Folklore, Function, Educational Values